Speech Prosody 2018 2018
DOI: 10.21437/speechprosody.2018-59
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Efficiency of Juncture Perception in L1 and L2

Abstract: In two experiments, Mandarin listeners resolved potential syntactic ambiguities in spoken utterances in (a) their native language (L1) and (b) English which they had learned as a second language (L2). A new disambiguation task was used, requiring speeded responses to select the correct meaning for structurally ambiguous sentences. Importantly, the ambiguities used in the study are identical in Mandarin and in English, and production data show that prosodic disambiguation of this type of ambiguity is also reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Participants' preference for the VP-attachment in unconscious processing can be explained by the Minimal Attachment principle. But other participants' preference for the NP-attachment suggests that Minimal Attachment principle cannot always predict L2 learners' parsing performance, and their parsing strategy, which is related to their linguistic experience, may have to be learned anew (Cutler, 2012;Ip and Cutler, 2018). That most of the participants' bias was reduced after they were informed of the ambiguity in Task 3 suggests that the learners could use prosodic cues to resolve ambiguity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants' preference for the VP-attachment in unconscious processing can be explained by the Minimal Attachment principle. But other participants' preference for the NP-attachment suggests that Minimal Attachment principle cannot always predict L2 learners' parsing performance, and their parsing strategy, which is related to their linguistic experience, may have to be learned anew (Cutler, 2012;Ip and Cutler, 2018). That most of the participants' bias was reduced after they were informed of the ambiguity in Task 3 suggests that the learners could use prosodic cues to resolve ambiguity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent decades have witnessed an increasing number of studies investigating how L2 learners process ambiguous sentences in spoken language comprehension. Some of the earlier studies have reported that L2 learners have difficulty in ambiguity resolution in spoken language comprehension, which may be attributed to their low sensitivity to prosodic cues, low L2 proficiency, difficulty in information integration, L1 background, limited learning experience, and limited cognitive resources, or that the L2 parsing strategy has to be learned anew (Harley et al, 1995;Ying, 1996;Dekydtspotter et al, 2008;Nakamura et al, 2016;Ip and Cutler, 2018;Nickels and Steinhauer, 2018). Our present study provides additional evidence that L2 learners' difficulty in prosodic disambiguation may come from their lack of ambiguity awareness that constrains them to detect the ambiguity within the structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation